Development of a scaffold incorporating zinc-oxide nano-particles for cartilage tissue engineering under physiological conditions / Eraj Humayun Mirza - Eraj Humayun, Mirza (2016)
Cartilage tissue is among the most complex of all in the human body. Degeneration of cartilage, lack of repair and various traumatic and pathological conditions among individuals increase joint pain and disability. Researchers have been trying to repair cartilage damage for decades, but have failed to achieve an optimal repair strategy. Cartilage tissue is adapted to low oxygen environments and this condition appears to be a key factor in the growth, regulation, and survival of chondrocytes; which are the only cells present in cartilage tissue. The present thesis defines the fabrication and characterisation of an antibacterial biomaterial for cartilage tissue repair. Furthermore, this thesis promotes the use of Zinc Oxide (ZnO) nanoparticles (NP) for better growth of cartilage cells and survival of cartilage tissue as a whole. Composite scaffolds and thin films of polyoctanediol citrate (POC) polyester elastomer, with varying concentrations (1wt%, 3wt% and 5wt%) of ZnO were fabricated by a solvent-casting/particulate-leaching and mould casting technique respectively. It was observed that material properties can be successfully controlled by simple variation of NP concentration within the composite. The ion release kinetics from ZnO-POC scaffolds are strongly dependent on NP concentration and degradation of pure POC matrix. All the composite scaffolds showed strong antibacterial characteristics. However, cell culture studies demonstrated that 1% ZnO incorporation in POC polymer is the optimal concentration for chondrocyte cells. Moreover, the effect of 1% ZnONP on chondrocyte proliferation and matrix synthesis cultured under normoxia (21% O2) and hypoxia (5% O2) demonstrated upregulation of chondrocyte proliferation and sulphated glycosaminoglycan (S-GAG) in hypoxic culture. A synergistic effect of oxygen concentration and 1% ZnONP in up-regulation of anabolic gene expression (Type II collagen (COL2A1) and aggrecan (ACAN)), and a down regulation of catabolic (MMP-13) gene expression was observed. Furthermore, iv production of transcription factor hypoxia-inducible factor 1A (HIF-1A) in response to hypoxic condition to regulate chondrocyte survival under hypoxia was not affected by the presence of 1% ZnONP. Lastly this thesis discusses the physiological adaptations of cartilage tissue in a dynamic mechanical loading and hypoxic condition to yield benefits of combined bio-factors for cartilage tissue engineering applications. The results indicate that the combination of dynamic loading is compatible with the nanoparticle addition. Furthermore, dynamic loading suppresses MMP-13, and increase the expression of COL2A1 and ACAN with an increase in cell viability, and promotion of rounded cell morphology (a phenotypic marker). It was concluded that POC-ZnONP scaffolds are of major importance in the development of multifunctional scaffolds based on biodegradable polyesters for cartilage tissue engineering and presence of 1% ZnONP appears to preserve homeostasis of cartilage in its hypoxic environment. While 1% ZnONP should be considered for beneficial incorporation into 3D hypoxic culture systems in the presence of mechanical stimulation. Further studies must focus on determining the use of 1% ZnONP in different polymers for use in various tissue engineering applications.